The ethics of discontinuing anti-retroviral therapy in frequently non-adherent adults infected with HIV - De Villiers, Maryke (Stellenbosch : Stellenbosch University, 2025)
De Villiers, Maryke. 2025. The ethics of discontinuing anti-retroviral therapy in frequently non-adherent adults infected with HIV. Unpublished masters thesis. Stellenbosch: Stellenbosch Univeristy [online]. Available: https://scholar.sun.ac.za/handle/10019.1/132134